English language teachers' knowledge, skills, and attitudes toward computer-aided language instruction and classroom performance - Borromeo, Josefina Ante 1963- (2007)
This study explored and described the English language teachers' knowledge, skills, and attitudes toward Computer-aided Language Instruction (CaLI). Research data were obtained through a survey using the Teachers' Attitudes Toward Computers test. Descriptive statistics was used to describe the English Teachers' attitudes toward computers. It was revealed that teachers' levels of knowledge and skills regarding computers improved markedly after CaLI training ang implementation. Knowledge of computers and their advantages were the primary factors for the participants' use while lack of computer units and knowledge were the reasons for their non-use.
"May 2007."
Vita.
Thesis (Ph.D. Education : Language Education)--University of the Philippines, Diliman.
Keywords: English teachers -- Philippines -- Camarines Sur -- Attitudes; English language -- Philippines -- Camarines Sur -- Computer-assisted instruction; English language -- Study and teaching (Higher) -- Philippines -- Camarines Sur